Real-time fluorescence growth curves for viable bacteria quantification in foods - Yajing Chen; Yanlin Chen; Siying Tang; Biao Tang; Shengbin He (Food Chemistry: X)
Here, for the first time, we used a membrane permeable fluorescent nucleic acid stain (SYBR Green) to trace the in-vivo DNA replication during bacterial binary fission. Such stain did not influence the growth of bacteria. Nor did the bacteria degrade the stain, enabling the fluorescent microplate reader to monitor sensitively the growth of the bacteria. Hence, a real-time fluorescence growth curve (RTFGC) method was put forward for the sensitive quantification of viable bacteria in foods. Using E. coli O157:H7 as a bacteria model, the RTFGC method could quantify bacteria within the range of 10 to 1 × 106 cfu/mL, with a linear correlation coefficient R2 of 0.997. It was found that melting curve was unique for a particular bacterial strain, which could be used for contamination identifications. Good practicability of the RTFGC in quantifying E. coli O157:H7 from tap water, juices, and milks was demonstrated.